Middle Eastern and African Perspectives on the Development of Public Relations Other Voices - Watson, T.; Watson, T. (National Perspectives on the Development of Public Relations, 2014)
The National Perspectives on the Development of Public Relations: Other Voices series is the first to offer an authentic world-wide view of the history of public relations. It will feature six books, five of which will cover continental and regional groups. This third book in the series focuses on the Middle East and Africa.